2019
DOI: 10.1111/ele.13210
|View full text |Cite
|
Sign up to set email alerts
|

Global photosynthetic capacity is optimized to the environment

Abstract: Earth system models (ESMs) use photosynthetic capacity, indexed by the maximum Rubisco carboxylation rate (V cmax), to simulate carbon assimilation and typically rely on empirical estimates, including an assumed dependence on leaf nitrogen determined from soil fertility. In contrast, new theory, based on biochemical coordination and co‐optimization of carboxylation and water costs for photosynthesis, suggests that optimal V cmax can be predicted from climate alone, irrespective of soil fertility. Here, we deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
279
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 190 publications
(303 citation statements)
references
References 68 publications
13
279
0
Order By: Relevance
“…First, if the correlation with leaf N content was the primary driver of the ability to estimate V c,max25 with spectra, it does not explain why leaf spectra show far higher predictive power than using leaf N content alone ( R 2 = 0.89 for leaf spectra in the present study vs R 2 = 0.31–0.33 for leaf nitrogen content as shown in Domingues et al ., and Norby et al ., ). Furthermore, the V c,max25 –leaf N relationship does not always hold up at the site level (Bahar et al ., ; Rogers et al ., ; Evans & Clark, ) and recent global syntheses have shown that variation in leaf N can only explain a small portion of variation in V c,max (Ali et al ., ; Smith et al ., ). Secondarily, many other studies suggest that in addition to leaf N content, other leaf traits, such as leaf phosphorus (P) content (Walker et al ., ; Norby et al ., ), leaf chlorophyll content (Croft et al ., ), LMA (Walker et al ., ) and age (Albert et al ., ), also are related to V c,max25 , and inclusion of more traits as predictive variables can significantly improve the power of trait based model to predict V c,max25 , compared with the just one trait, leaf N content (Walker et al ., ).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…First, if the correlation with leaf N content was the primary driver of the ability to estimate V c,max25 with spectra, it does not explain why leaf spectra show far higher predictive power than using leaf N content alone ( R 2 = 0.89 for leaf spectra in the present study vs R 2 = 0.31–0.33 for leaf nitrogen content as shown in Domingues et al ., and Norby et al ., ). Furthermore, the V c,max25 –leaf N relationship does not always hold up at the site level (Bahar et al ., ; Rogers et al ., ; Evans & Clark, ) and recent global syntheses have shown that variation in leaf N can only explain a small portion of variation in V c,max (Ali et al ., ; Smith et al ., ). Secondarily, many other studies suggest that in addition to leaf N content, other leaf traits, such as leaf phosphorus (P) content (Walker et al ., ; Norby et al ., ), leaf chlorophyll content (Croft et al ., ), LMA (Walker et al ., ) and age (Albert et al ., ), also are related to V c,max25 , and inclusion of more traits as predictive variables can significantly improve the power of trait based model to predict V c,max25 , compared with the just one trait, leaf N content (Walker et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…This assumption is most questionable for the tropical forest biome where forests hold enormous plant functional diversity (Condit et al ., ; Steege et al ., ; Asner et al ., ) that includes diversity in photosynthetic capacity (Norby et al ., ; Walker et al ., ). Furthermore, for a given species, V c,max25 has been shown to vary greatly with leaf development, growth temperature, and water and nutrient availability (Medlyn et al ., ; Wilson et al ., ; Kenzo et al ., ; Kattge & Knorr, ; Ali et al ., ; Norby et al ., ; Albert et al ., ; Kumarathunge et al ., ; Smith et al ., ). Recently it was shown that the seasonality of photosynthesis in Amazonian evergreen forests, a c .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…This finding suggests that N area is not the main determinant of either V cmax or R d (Table ). Second, global patterns of variation in V cmax have been shown to be predictable from climate alone (Smith et al, ), suggesting that V cmax,25 (and therefore R d,25 ) is not determined by N area , but rather primarily by photosynthetic potential—which is set by the local climatic environment. This potential in turn determines the metabolic component of N area .…”
Section: Discussionmentioning
confidence: 99%
“…Co‐limitation is optimal in an eco‐evolutionary sense because any other outcome would either incompletely exploit available light, or require additional respiration to maintain excess amounts of Rubisco. This hypothesis explained 64% of field‐measured V cmax,tg variability in C 3 plants across different biomes, and has been used with success to predict global patterns of primary production (Smith et al, ; Wang, Prentice, Keenan, et al, ). Second, the various metabolic functions of R d in mature leaves are assumed to be tightly coupled to V cmax (Step 3 in Figure )—implying a close link between the acclimation of V cmax and R d .…”
Section: Introductionmentioning
confidence: 99%